Advancing cryptococcal treatment: The role of nanoparticles in mitigating antifungal resistance - Rahul Harikumar Lathakumari; Leela Kakithakara Vajravelu; Abhishek Satheesan; Jayaprakash Thulukanam (Current Research in Microbial Sciences)
Cryptococcus, a ubiquitous and formidable fungal pathogen, contributes to a substantial global disease burden, with nearly 250,000 cases and 181,000 fatalities attributed to cryptococcal meningitis annually worldwide. The invasive nature of Cryptococcus presents significant challenges in treatment and management, as it mostly affects vulnerable populations, including HIV patients, organ transplant recipients, pregnant women, and elderly individuals. Moreover, these difficulties are exacerbated by the development of antifungal resistance, which emphasizes the need for efficient control measures. In this context, research efforts focusing on infection control and novel therapeutic strategies become paramount. Nanoparticle-based therapies emerge as a solution, offering advanced antifungal properties and improved efficacy. Developing effective treatment options requires understanding the complex landscape of cryptococcal infections and the innovative potential of nanoparticle-based therapies. This review highlights the urgent need for novel strategies to combat the growing threat posed by antifungal resistance while offering insights into the intricate realm of cryptococcal infections, particularly focusing on the promising role of nanoparticle-based therapies.